(untitled) (Research, Society and Development, 2024)
The objective of the work was to verify the physiological and biochemical performance of barley seeds treated and stored for short periods of time. The cultivars BRS Cauê and BRS Rubi were used, the control and seed treatments Fipronil BRT 250 FS, Baytan FS, Certeza N, Cruiser Opti and Standak Top and storage times of 0, 7, 14, 21 and 28 days, being a three-factorial experiment (2x6x5), in a completely randomized design. Germination, length and dry mass of shoots and roots, enzymatic antioxidant activity of SOD, CAT and APX, lipid peroxidation, quantification of hydrogen peroxide and total soluble sugar content were evaluated. The BRS Rubi cultivar was more sensitive in terms of physiological quality to the seed treatments used, mainly Baytan, and across storage periods. The biochemical performance was affected by the Standak Top treatment for the BRS Cauê cultivar, reducing antioxidant activity, increasing lipid peroxidation and the amount of hydrogen peroxide. Storage of treated barley seeds for a short period of time altered the physiological and biochemical performance of the seeds. The BRS Rubi cultivar is more sensitive to the seed treatments used and storage periods regarding germination. Chemical treatment can reduce germination, shoot and root length and negatively modify the enzymatic response of SOD, CAT and APX. Seed treatment within 14 days can contribute to safer sowing.